2018
DOI: 10.1038/s41467-018-06086-4
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo neutralization of dendrotoxin-mediated neurotoxicity of black mamba venom by oligoclonal human IgG antibodies

Abstract: The black mamba (Dendroaspis polylepis) is one of the most feared snake species of the African savanna. It has a potent, fast-acting neurotoxic venom comprised of dendrotoxins and α-neurotoxins associated with high fatality in untreated victims. Current antivenoms are both scarce on the African continent and present a number of drawbacks as they are derived from the plasma of hyper-immunized large mammals. Here, we describe the development of an experimental recombinant antivenom by a combined toxicovenomics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
158
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(162 citation statements)
references
References 27 publications
4
158
0
Order By: Relevance
“…Recombinant antivenoms containing several monoclonal antibodies or single-chain variable fragments (scFv) that target CTXs may be a promising source material for solving the problem of N. atra-induced local tissue damage. A previous study reported a situation similar to our case [56], showing that the currently used equine polyvalent antivenom exhibited a limited ability to neutralize dendrotoxin-mediated neurotoxicity. In this case, the researchers developed a cocktail of a few humanized monoclonal antibodies against this neurotoxin.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Recombinant antivenoms containing several monoclonal antibodies or single-chain variable fragments (scFv) that target CTXs may be a promising source material for solving the problem of N. atra-induced local tissue damage. A previous study reported a situation similar to our case [56], showing that the currently used equine polyvalent antivenom exhibited a limited ability to neutralize dendrotoxin-mediated neurotoxicity. In this case, the researchers developed a cocktail of a few humanized monoclonal antibodies against this neurotoxin.…”
Section: Discussionsupporting
confidence: 86%
“…Several advanced biotechnological tools have recently been adopted for developing alternative strategies for antivenom production [53,54]. Applying expertise in synthetic biology, antibody research and immunology, a number of researchers have attempted to develop recombinant antivenoms and investigate their ability to neutralize toxins from snake venom [55][56][57][58][59]. Recombinant antivenoms containing several monoclonal antibodies or single-chain variable fragments (scFv) that target CTXs may be a promising source material for solving the problem of N. atra-induced local tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, new strategies capable of circumventing variation in snake venom composition to deliver broad neutralization across snake species, while simultaneously improving the safety, affordability and storage logistics of treatment, are urgently needed 3,47 . Approaches showing signs of promise include the rational design of immunogens to improve the neutralizing breadth of conventional products 48 , the selection of human or humanized toxin-specific monoclonal or oligoclonal antibodies 49,50 , and the use of small molecule inhibitors specific to certain toxin families 12 , such as the PLA 2 -inhibitor varespladib 22,26,27 and the metal chelator DMPS 28 23 , we found both drugs to be equipotent in vitro. We selected marimastat as our candidate for in vivo efficacy experiments due to a number of desirable characteristics that make it amenable for a future field intervention for snakebite, specifically its oral vs.…”
Section: Discussionmentioning
confidence: 85%
“…To better mimic a real-life envenoming scenario, we next tested the marimastat and varespladib inhibitor mixture in a preclinical 'challenge then treat' model of envenoming, where the venom is first administered intraperitoneally and then the test therapy is administered intraperitoneally separately after the venom challenge 28 . To this end, we injected venom from each of the five viper species in doses equivalent to at least 5 x the intravenous (iv) LD 50 'envenomed' mice. This observation was noted for both the 'intravenous preincubation' and 'intraperitoneal challenge then treat' models of envenoming ( Fig.…”
Section: Administration Of the Marimastat And Varespladib (Mv) Dual Tmentioning
confidence: 99%
“…Such studies have stimulated much research into the development of novel therapeutic approaches to tackle snakebite. These include the use of monoclonal antibody technologies to target key pathogenic toxins found in certain snake species (Laustsen et al, 2018;Silva et al, 2018), pathology rather than geographically-focused approaches to neutralizing venom toxins (Ainsworth et al, 2018), and the use of small molecule inhibitors designed to generically target specific toxin classes (Arias et al, 2017;Bryan-Quiros et al, 2019). The priority targets for these "next generation" snakebite therapeutics are the multifunctional toxins described herein (PLA2s, SVMP, SVSP, 3FTX) because of the major pathologies that they cause in snakebite victims.…”
Section: Therapeutic Implications Treating Snake Envenomationmentioning
confidence: 99%